Inverse identification of the material parameters of a nonlinear concrete constitutive model based on the triaxial compression strength testing (Fracture and Structural Integrity, 2016)
The aim of this paper is to perform the inverse identification of the material parameters of a nonlinear constitutive model intended for the modeling of concrete which is known as the Karagozian & Case Concrete model. At present, inverse analysis is frequently used because it allows us to find the optimum parameter values of nonlinear material models. When applying such parameters, the resulting response of the structure obtained from a computer simulation is very similar to the real response of the structure based on the related experimental measurement. This condition then undoubtedly constitutes one of the progressive steps to refine the current numerical approaches. For the purposes of the inverse analysis performed in this paper the experimental data was obtained from the triaxial compression strength tests carried out on the concrete cylinders.
Keywords: Inverse analysis; Optimization; Objective function; Numerical simulation; Nonlinear concrete material model; Experimental data